A Stylistic and Semantic Analysis of the Word Qalb in the Quran: Insights from the Process of Knowledge Acquisition - Maulani, Hikmah; Rohanda; Kodir, Abdul; Aladdin, Ashinida (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
This study investigates the meaning of the word qalb in the Qur’an through a stylistic and semantic lens, with particular attention to its role in the process of human knowledge acquisition. Employing a qualitative-descriptive methodology and textual analysis of selected Qur’anic verses, the research explores the stylistic expressions and semantic nuances of qalb within contexts related to cognitive, affective, and spiritual functions. The findings qalb operates as an integrative faculty, synthesizing intuition, inner experience, and rationality processing reality and meaning in a holistic manner. The stylistic analysis reveals that references to qalb frequently appear in rhetorically charged structures aimed at evoking moral and spiritual consciousness, particularly in warnings against hardness of heart, calls for introspection, and reminders of the consequences of ignoring divine guidance. These findings affirm qalb as an epistemological construct inherently intertwined with the process of apprehending divine truth, which cannot be reduced to or replaced by the notions of ʿaql (intellect) or shadr (chest).